-6(4m-4)+4m=-8-7(2m+4)

Simple and best practice solution for -6(4m-4)+4m=-8-7(2m+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(4m-4)+4m=-8-7(2m+4) equation:



-6(4m-4)+4m=-8-7(2m+4)
We move all terms to the left:
-6(4m-4)+4m-(-8-7(2m+4))=0
We add all the numbers together, and all the variables
4m-6(4m-4)-(-8-7(2m+4))=0
We multiply parentheses
4m-24m-(-8-7(2m+4))+24=0
We calculate terms in parentheses: -(-8-7(2m+4)), so:
-8-7(2m+4)
determiningTheFunctionDomain -7(2m+4)-8
We multiply parentheses
-14m-28-8
We add all the numbers together, and all the variables
-14m-36
Back to the equation:
-(-14m-36)
We add all the numbers together, and all the variables
-20m-(-14m-36)+24=0
We get rid of parentheses
-20m+14m+36+24=0
We add all the numbers together, and all the variables
-6m+60=0
We move all terms containing m to the left, all other terms to the right
-6m=-60
m=-60/-6
m=+10

See similar equations:

| y+3=2y=11 | | 6(z–8)=24 | | 3+2x=-16 | | 7(1+5x)=112 | | 3h=–10+8h | | n+7.1=8.5 | | x-27.5=10.5 | | 0=q–45 | | 5x=8-3x-2 | | 987-987p=98 | | 2x+27=12x-64 | | 7+165+8y-75=180 | | 4x+39=7x-47 | | .5x=40.4 | | 12+26+x+38+x=x+3 | | x-8=x-7 | | 1057=b+678 | | 1+11=(2x+1)+1 | | x+255=315 | | k/9+7=6 | | 110+y+5y-20=180 | | 12+x+35+26+x=38+x | | x/42=6 | | 12+26+x+38+x=x+35 | | 1/2x-2=2/3x+6 | | 3=x+-3-5x | | 9(x+3=7x-3 | | x+38=−3 | | x+3/8=−3 | | 4.8x-8=-57 | | x+(.0946882x)=40.08 | | 9(x+3)=x-8x |

Equations solver categories